Answer:
x=7
Explanation:
First, you start with keep, change, change. Keep the x, change the minus to a plus, and then make the negative 3 into three.
So you should have X+3=10
Take the 10 and minus 3
Then you have 7
So your answer will be X=7
x = 7
Rule: an even number of - signs written one after another produces a plus number.
So - - 3 = 3
The rule also lets you do something strange like
- - - - 4 = 4 but you hardly ever see this.
Rule: an odd number of minus signs produces a minus number.
x + 3 = 10 Subtract 3 from both sides.
x + 3 - 3 = 10 - 3
5.6m questions
7.3m answers